1998
DOI: 10.1212/wnl.50.6.1907
|View full text |Cite
|
Sign up to set email alerts
|

Root stimulation studies in the evaluation of patients with motor neuron disease

Abstract: Nerve root stimulation may be employed in patients with motor neuron disease (MND) to rule out motor neuropathy with conduction block. The diagnostic utility of these studies is unknown, in part because the range of amplitude changes across nerve root segments in patients with active neuronal degeneration has not been well studied. We reviewed root stimulation studies in 32 patients (59 nerves) with MND and found segmental amplitude reduction from 0 to 45%, a range similar to values reported for normal subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Nevertheless, root stimulation does not disclose proximal conduction block in ALS patients. 46 The F wave is a late response that results from the antidromic activation of one or a small number of motoneurons following peripheral nerve stimulation. 18,28,39 F waves are probably preferentially generated by depolarization at the low-threshold initial segment of large neurons with subsequent invasion of the soma; most antidromic impulses are blocked in the axon hillock of the motoneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, root stimulation does not disclose proximal conduction block in ALS patients. 46 The F wave is a late response that results from the antidromic activation of one or a small number of motoneurons following peripheral nerve stimulation. 18,28,39 F waves are probably preferentially generated by depolarization at the low-threshold initial segment of large neurons with subsequent invasion of the soma; most antidromic impulses are blocked in the axon hillock of the motoneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Root stimulation is particularly difficult, and it requires well-defined normal values for comparison. 117 Although the conduction block may appear at any level, the median nerve in the forearm is a common site rarely susceptible to other disorders. The best evidence of multifocal motor conduction block is a localized region of CMAP amplitude drop or slowing over a few centimeters, demonstrated by "inching" or near-nerve needle stimulation.…”
Section: Motor Unit Number Estimates (Munes)mentioning
confidence: 99%
“…It has been suggested that cervical root stimulation, either transcutaneously or by using a needle, be used to quantify CB in proximal segments. 16 18 19 Patients with ALS may have a greater degree of CMAP reduction in the proximal segments than in normal subjects because of abnormal temporal dispersion in fibres undergoing active degeneration. 16 It is therefore important to determine the degree of CMAP reduction that can be found, not only in healthy controls but also in ALS.…”
mentioning
confidence: 99%